Metal-free radical trifluoromethylation of beta-nitroalkenes through visible-light photoredox catalysis - Midya, Siba P.; Rana, Jagannath; Abraham, Thomas; Aswin, Bhaskaran; Balaraman, Ekambaram (Chemical Communications, 2017)
A catalytic method for functional group interconversion is immensely important in modern sciences. Here, we report an efficient catalytic conversion of nitroalkenes to highly stereoselective 1-trifluoromethylalkenes at room temperature. This unprecedented metal-free photocatalytic strategy is simple and operates under visible-light irradiation using the commercially available CF3 source.

Manganese-catalyzed direct C-C coupling of -C-H bonds of amides and esters with alcohols via hydrogen autotransfer - Rana, Jagannath; Gupta, Virendrakumar; Balaraman, Ekambaram (Dalton Transactions, 2019)
Herein we report an efficient manganese-catalyzed C-alkylation of unactivated amides and tert-butyl acetate using alcohols as alkylating agents. This elegant approach exhibits a broad substrate scope providing the C-C coupled products of amides via a hydrogen auto-transfer strategy using aryl, heteroaryl, and aliphatic alcohols.